Literacy and self-criticism about information behaviour through the graphic humor of El Roto and Mauro Entrialgo - Gómez-Hernández, José-Antonio (Anuario ThinkEPI, 2012)
Taking advantage of political cartoons by El Roto and Mauro Entrialgo, the need for a critical use of information technology and the internet is presented. Information and communication technologies (ICT) have generated high hopes, being seen as tools to democratize knowledge and information. However, to make good use of their potential we must know their limits, what changes they generate in our behavior and how they affect our privacy, identity or personal relationships. The above mentioned cartoonists help to generate self-criticism of our information behaviour, fostering a rational information literacy, with a thoughtful and intentional use of technologies and networks.